KAJIAN SISTEMATIS PERILAKU NONLINIER SAMBUNGAN BAUT PADA STRUKTUR BAJA DAN IMPLIKASINYA TERHADAP PENERAPAN SNI 1729:2020 - Oktavianus Chayadi; Edison Hatoguan Manurung; Abdul Mubarok (SINERGI : Jurnal Riset Ilmiah, 2026)
In the studies reviewed, bolted connections in steel structures generally exhibit semi-rigid behavior with a nonlinear moment-rotation response, where the majority of studies report behavior lying between the perfect pin and fully rigid conditions. The authors have not identified a review that simultaneously synthesizes rotational stiffness, bolt slip effects, and implications for SNI 1729:2020 within a single integrated framework; similar reviews in the Indonesian standards context remain scarce based on searches across Scopus, ScienceDirect, and Google Scholar. This study presents a systematic literature review following the PRISMA 2020 protocol (Page et al., 2021), examining 13 selected studies from 75 identified articles (search conducted 15–20 June 2026). The 2017–2025 timeframe was selected to capture recent developments in nonlinear analysis and FEM of bolted connections. Quality assessment using an internal scoring instrument adapted from JBI principles yielded scores ranging from 2 to 5 out of 5, reflecting realistic methodological quality variation. Qualitative synthesis reveals a consistent tendency that increasing end-plate thickness produces a significant increase in initial rotational stiffness, accompanied by a moderate-to-significant reduction in rotation capacity. Neglecting bolt slip was found to tend toward significant displacement prediction errors near ultimate capacity. Comparison of SNI 1729:2020 and Eurocode 3 identifies three aspects not yet explicitly accommodated in SNI 1729:2020, potentially addressable through Eurocode 3 component method adoption with Indonesian condition validation.